Inovasi strategi Berdiferensiasi Manajemen Berbasis Sekolah (MBS) untuk mengatasi kesenjangan hasil Belajar Mahasiswa - Lumi, Sjerly M.; Lumentah, Lenda; Gumerung, Jeffry (Peneliti.net, 2025)
Socio-economic background, access to learning and learning styles as well as technology and resources so that the gap in learning outcomes in students is a complex problem in terms of the quality of graduates, as well as the development of human resource potential. So that a new breakthrough in strategic innovation that is differentiated with School-Based Management in Higher Education is needed. The flexibility of Higher Education with School-Based Management can adjust to management and learning strategies with the unique needs of students, so that it has the potential to overcome the gap in learning outcomes. School-Based Management is autonomous, so that each Higher Education can develop the strategy that best suits its context, where leaders, lecturers, students and even parents of students and the community are a collaboration in the implementation of School-Based Management. With this collaboration, programs will run effectively. This study aims to determine the Innovation of Differentiated School-Based Management (MBS) strategies to overcome the gap in Learning outcomes of FKIP Students majoring in Economic Education UKIT. This research method is qualitative research, qualitative research is used because it can be used to analyze the study of a comprehensive phenomenon from an observation, the approach used is a descriptive approach. Data collection techniques are obtained through observation and interviews. The data analysis was carried out inductively, namely drawing conclusions taken from specific facts and then drawing general conclusions. The results of this study: learning gaps in FKIP students in the Department of Economic Education include 1), in utilizing free learning platforms, lecturers conduct initial evaluations to identify student learning needs. Furthermore, based on the results of the evaluation, a learning plan is prepared, and lecturers prepare teaching materials in the form of modules. 2), differentiation does not mean changing all elements in teaching. 3). Differentiated learning strategies implemented within the MBS (School-Based Management) framework have proven effective in reducing learning gaps between students